Changes in lipids and volatile compounds of oat flours and extrudates during processing and storage. (March 2015) - Lampi, Anna-Maija; Damerau, Annelie; Li, Jia; Moisio, Timo; Partanen, Riitta; Forssell, Pirkko; Piironen, Vieno
Abstract: Oats is valuable raw material, but it needs to be heat-treated to inactivate lipid degrading enzymes that would deteriorate its sensory quality. The aim was to study if extrusion could replace traditional heat treatment in production of whole meal oats with stable lipids. Flours from non-heat-treated (NHT) oat grains were extruded under four conditions and subjected to 15-week storage. Stability of the extrudates as well as the NHT and heat-treated oat grains were studied for hydrolytic and oxidative reactions by measuring neutral lipid profiles and volatile products. In the NHT oat grains, lipid hydrolysis started immediately after milling, which also promoted lipid oxidation during storage. Enzymatic degradation of lipids could effectively be prevented by extrusion even at the lowest temperature of 70 °C. The extrusion temperature could be increased to 110 °C without subjecting the lipids to non-enzymatic oxidation. However, by increasing the temperature to 130 °C, lipid oxidation was promoted, which also resulted in losses of neutral lipids over time. Hexanoic acid became the major volatile product in oat extrudates during extensive lipid oxidation instead of hexanal, which is a commonly used lipid oxidation indicator. In conclusion, lipids in oat grains could be stabilized by extrusion even at a temperature of 70 °C. Highlights: Traditional heat-treatment can be replaced by extrusion in the production of stable oat products. Extrusion temperature of 70 °C was enough to inactivate lipid degrading enzymes in oats. Extrusion temperature of 130 °C subjected the lipids to non-enzymatic oxidation. Hexanal or hexanoic acid were the major volatile lipid oxidation products in the extrudates.